Synthesis and biological evaluation of 1-(2-hydroxy-3-phenyloxypropyl)piperazine derivatives as T-type calcium channel blockers - Park, Jung-eun; Ji, Wan Keun; Jang, Jae Wan; Pae, Ae Nim; Choi, Keehyun; Choi, Ki Hang; Kang, Jahyo; Roh, Eun Joo (Pergamon Press Ltd., 2013)
To obtain selective and potent inhibitor for T-type calcium channel by ligand based drug design, 2-hydroxy-3-phenoxypropyl piperazine derivatives were synthesized and evaluated for in vitro activities. Compound 6m and 6q showed high selectivity over hERG channel (IC50 ratio of hERG/alpha(1G) 6m = 8.5, 6q = 18.38) and they were subjected to measure pharmacokinetics profiles. Among them compound 6m showed an excellent pharmacokinetic profile in rats. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: CA2+ CHANNELS; INHIBITION; TARGETS